What Can Integrated Analysis of Morphological and Genetic Data Still Reveal about the Anastrepha fraterculus (Diptera: Tephritidae) Cryptic Species Complex? - Leandro F. Prezotto; André L.P. Perondini; Vicente Hernández-Ortiz; Daniel Frías; Denise Selivon (Insects, 2019)
The South American fruit fly Anastrepha fraterculus (Wiedemann) is a complex of cryptic species, the so-called “Anastrepha fraterculus complex”, for which eight morphotypes are currently recognized. A previous analysis of ITS1 in samples of the Anastrepha fraterculus complex, while revealing high distinctiveness among samples from different localities of South America, Central America, and Mexico, no direct association was made between sequence type and morphotype. In the present report, a correlated analysis of morphometry and ITS1 data involved individuals belonging to the same population samples. Although showing a low level of intra-populational nucleotide variability, the ITS1 analysis indicated numerous inter-population sequence type variants. Morphotypes identified by morphometric analysis based on female wing shape were highly concordant with ITS1 genetic data. The correlation of genetic divergence and morphological differences among the tested samples gives strong evidence of a robust dataset, thereby indicating the existence of various taxonomic species within the A. fraterculus complex. However, the data revealed genetic and morphological variations in some regions, suggesting that further analysis is still required for some geographic regions.